The capability to synthesize phytochelatins and the presence of constitutive and functional phytochelatin synthases are ancestral (plesiomorphic) characters for basal land plants - Petraglia, Alessandro (Journal of experimental botany, 2014)
Bryophytes, a paraphyletic group which includes liverworts, mosses, and hornworts, have been stated as land plants that under metal stress (particularly cadmium) do not synthesize metal-binding peptides such as phytochelatins. Moreover, very little information is available to date regarding phytochelatin synthesis in charophytes, postulated to be the direct ancestors of land plants, or in lycophytes, namely very basal tracheophytes. In this study, it was hypothesized that basal land plants and charophytes have the capability to produce phytochelatins and possess constitutive and functional phytochelatin synthases. To verify this hypothesis, twelve bryophyte species (six liverworts, four mosses, and two hornworts), three charophytes, and two lycophyte species were exposed to 0-36 μM cadmium for 72 h, and then assayed for: (i) glutathione and phytochelatin quali-quantitative content by HPLC and mass spectrometry; (ii) the presence of putative phytochelatin synthases by western blotting; and (iii) in vitro activity of phytochelatin synthases. Of all the species tested, ten produced phytochelatins in vivo, while the other seven did not. The presence of a constitutively expressed and functional phytochelatin synthase was demonstrated in all the bryophyte lineages and in the lycophyte Selaginella denticulata, but not in the charophytes. Hence, current knowledge according to phytochelatins have been stated as being absent in bryophytes was therefore confuted by this work. It is argued that the capability to synthesize phytochelatins, as well as the presence of active phytochelatin synthases, are ancestral (plesiomorphic) characters for basal land plants